2011
DOI: 10.3892/ijmm.2011.607
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition enhances etoposide-induced cell death in human hepatoma G2 cells

Abstract: Abstract. Induction of autophagy usually acts as a survival mechanism of cancer cells in response to chemotherapy. However, the function and molecular mechanism of autophagy in human hepatoma cells under drug treatment is still not clear. To address this issue, we established an experimental model in which HepG2 cells were treated with etoposide, a widely used anticancer agent. We demonstrate the etoposide-induced accumulation of GFP-LC3 dots by fluorescent microscopy, the up-regulation of Lc3-II protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…Findings of a recent study showed that berberine extracts promoted autophagy by activating beclin 1 expression and activated caspase-9 to induce apoptosis in hepatoma cells (25). Plant lectin from Polygonatum cyrtonema induced apoptosis and autophagy by inhibiting the Ras/Raf and PI3K/Akt signaling pathways in murine fibrosarcoma cells (26). In this study, the selective COX-2 inhibitor celecoxib, not only generated morphological changes indicative of apoptosis, but also typical changes of autophagy to include cytoplasmic autophagic vacuoles and autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of a recent study showed that berberine extracts promoted autophagy by activating beclin 1 expression and activated caspase-9 to induce apoptosis in hepatoma cells (25). Plant lectin from Polygonatum cyrtonema induced apoptosis and autophagy by inhibiting the Ras/Raf and PI3K/Akt signaling pathways in murine fibrosarcoma cells (26). In this study, the selective COX-2 inhibitor celecoxib, not only generated morphological changes indicative of apoptosis, but also typical changes of autophagy to include cytoplasmic autophagic vacuoles and autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…This increase of autophagy in the glaucomatous retina may act to recycle damaged material and lead to cell death. Depending on the cellular milieu, autophagy, as a lysosome-mediated self-degradation process of eukaryotic cells, can either promote survival or act as an alternative mechanism of PCD for neurons ( 6 , 22 ). Autophagy, as a defense mechanism for the removal of toxic multimeric complexes and aggregated proteins in neurodegenerative diseases, may also occur for self-digestion and self-clearance and the suppression of basal autophagy may cause neurodegeneration ( 6 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that other cell death pathways, such as autophagy, necrosis or pyroptosis (caspase-1-dependent inflammation), could also contribute to the enhanced efficacy of the combination in vivo. Etoposide has been reported to induce autophagy in certain cells 36 and it is known that caspase activation can also be induced in glioma cells undergoing autophagy 37 . The differences in the extent of apoptosis amongst the cells may potentially be due to p53 status or activation of Cdk1 checkpoint but further studies may be required to understand this 38 .…”
Section: Discussionmentioning
confidence: 99%